Research Seminars associated to BRU-IUL - Loureiro, S. M. C. (Research Seminars associated to BRU-IUL, 2018)
Research Seminars associated to BRU-IUL: invitation of professors, such as Prof. Avichai Shuv-Ami (Associate Professor in the Department of Marketing, School of Business Administration, Peres Academic Center in Israel) and Prof. Victoria Bellou (Associate Professor in the Department of Economics, University of Thessaly in Greece, and is a member at the Greek Open University)., April 20, 2018.